2017
DOI: 10.18632/oncotarget.15507
|View full text |Cite
|
Sign up to set email alerts
|

RAB10 overexpression promotes tumor growth and indicates poor prognosis of hepatocellular carcinoma

Abstract: Hepatocellular carcinoma (HCC), one of the most common and lethal cancers worldwide, has a high recurrence rate with current treatment modalities. Identifying biomarkers for early diagnosis and discovering new sufficient molecular targets for the development of targeted therapies are urgently needed. RAB10, a member of the RAS family, has been shown to be highly expressed in HCC. However, the function of RAB10 in HCC is less studied. Here we report that RAB10 acts as an oncogene in HCC. The shRNA-mediated knoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(50 citation statements)
references
References 29 publications
1
48
0
Order By: Relevance
“…Elevated expression of IL‐8 was validated in activated neoHFFs using fluorescent microscopy (Figure S4B, Supporting Information). Indeed, both Rab10a and NDRG1 have been shown to promote section of IL‐8 . Cancer cells release Exos that stimulate stromal cells to secrete IL‐8 that, in turn, modulates angiogenesis and leukemia cell survival .…”
Section: Resultsmentioning
confidence: 99%
“…Elevated expression of IL‐8 was validated in activated neoHFFs using fluorescent microscopy (Figure S4B, Supporting Information). Indeed, both Rab10a and NDRG1 have been shown to promote section of IL‐8 . Cancer cells release Exos that stimulate stromal cells to secrete IL‐8 that, in turn, modulates angiogenesis and leukemia cell survival .…”
Section: Resultsmentioning
confidence: 99%
“…19,20 Recently, Rab10 has been demonstrated to be aberrantly expressed in some types of cancers and show biological signicance in cancer progression. [21][22][23] However, the specic role of Rab10 in thyroid cancer remains unknown.…”
Section: Introductionmentioning
confidence: 99%
“…12 Moreover, increased Rab10 expression has been linked to poor prognosis in HCC accompanied by pathological complications such as distant metastasis. 29 Rab10 was also identified as an oncogene due to the evidence that shRNA-mediated knockdown of Rab10 resulted in a reduction of HCC cell proliferation and colony formation. 29 Also, a recent study demonstrated that Rab10 was highly expressed in some liver cancer tissue samples.…”
Section: Discussionmentioning
confidence: 99%
“…29 Rab10 was also identified as an oncogene due to the evidence that shRNA-mediated knockdown of Rab10 resulted in a reduction of HCC cell proliferation and colony formation. 29 Also, a recent study demonstrated that Rab10 was highly expressed in some liver cancer tissue samples. 30 Furthermore, inhibition of Rab10 repressed osteosarcoma cell proliferation and metastasis, and its expression was negatively regulated by miR-329.…”
Section: Discussionmentioning
confidence: 99%